UJI KINERJA DAN PENGUJIAN LAPANGAN MESIN GRADING TOMAT (Lycopersicum esculentum) TEP-5 - Sugandi, Wahyu K; -, Sudaryanto; Herwanto, Totok (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2017)
Laboratory of Agricultural Equipment and Machinery, Department of Industrial Engineering and Management Agricultural has designed a tomato grading machine TEP-5 to accelerate post-harvest handling of tomatoes. The Machine design need to be evaluated to determine it’s performance and quality of tomato grading results. The research method is descriptive analysis. Based on test results, tomato grading machine TEP-5 had an actual capacity of 4246 Tomato with the engine efficiency of 60,48% and. Engine noise no with and without load was 68,3dB and 69,8 dB respectively. Engine vibration generated during no-load test was 2.09 m/s 2 and 2.02 m/s 2 with load test. Engine power with and without load respectively 265,8 and 254,8 watt. Tomato quality results from machine was grading significantly diferrent as compared with the one graded manually. The level of tomato demage result from grading machine storage at room temperature and cool temperature (<10 o )respectively 6.42% and 5.61%. These values were lower as compared to the manual grading. The bruised area of tomato gradeded mechanicaly was 30,19% than that of tomato graded manually. Tomato color was the range of yellow and no difference was observed between manual and mechanical grading. Keyword: grading machine, test performance, self life.